WATER EDUCATION IN GHANA: EMPOWERING PEOPLE FOR SUSTAINABLE DEVELOPMENT - Kwoyiga, L.; Apusigah, A. A. (UDS International Journal of Development, 2023)
The role of education in promoting Sustainable Development has been recognized globally, culminating in the United Nations Decade of Education for Sustainable Development. However, unlike Environmental Education, education about water resources is given less attention despite the escalating water challenges in the world. Water is barely considered in most research literature by environmental academics and teacher educators. Nonetheless, recently, there has been a renewed interest in Water Education in higher educational institutions such as universities as a tool for promoting water knowledge and participation in decisions. Ghana is not only endowed with water resources but also besieged with water challenges such as fallen groundwater tables, stressed surface water resources, transboundary water issues and hydrometeorological-related disasters. Therefore, the study intended to identify in Ghanaian public universities the nature of the existing Water Education programmes, the emerging water issues that need attention and the reasons for the absence of these programmes. Guided by expert responses of academics and researchers in water and its related fields, primary data were generated for the study. Also, a desktop review of policy documents, articles and programmes’ information at universities’ websites in Ghana provided useful secondary data. The study revealed that out of the ten Ghanaian public universities studied, five of them do not have programmes relating to the subject of water. Notably, two universities established to deal with the environment and natural resources are among the five universities without water related programmes. It emerged that issues such as coping with extreme hydrological disasters, water diplomacy, gender and water utilization need educational attention too. This notwithstanding, funding of water programmes has been identified as a major challenge that universities face. Keywords: Water; Education; Sustainable Development; Universities; Ghana